Pengaruh Penerapan Prinsip Leadership, Employee Involvement, dan Continuous Improvement terhadap Kepuasan Kerja Karyawan - Aderia Putri Prasanti; Nyoman Anita Damayanti (Universitas Airlangga, 2015)
ABSTRACT Job satisfaction rate of Rumah Sakit Mata Undaan Surabaya (RSMU)’s employees increasedfrom 76,92% to 78,92% in 2012-2013. Unfortunately, in 2014 this rate decreased to 74,91%. The target set by management is 80%. Therefore, job satisfaction rate of RSMU’s employees has not reached the target. The aim of this study is to analyze the influence of leadership, employee involvement, and continuous improvement principle implementationtowards the job satisfaction of RSMU’s employees. This study used observational method with cross sectional design. The data was obtained through questionnaire with simple random sampling involving 90 employees as the sample of the research. The next step is analyzing the data analytically by using logistic regression test univariate (α=0,05) to examine the influence of leadership, employee involvement, and continuous improvement principle implementation towards the employee’s job satisfaction. The test result indicates that there are influences of two principles implementation towards the employee’s job satisfaction. Those principles, on the one hand, are leadership (sig=0,002) and continuous improvement (sig=0,006). On the other hand, the implementation of employee involvement does not affect the job satisfaction.Keywords :Employee job satisfaction, leadership, employee involvement, continuous improvement